Assessing the performance of a macroeconomic model - Juhana Hukkinen; Matti Virén (Bank of Finland, 1995)
This paper contains a description of a small quarterly model for the Finnish economy model (formerly, the QMED model).In addition to the basic features of this macroeconomic model, we report results from some stochastic simulations which illustrate the model's properties.Thus, the role of uncertainty in both endogenous and exogenous variables is scrutinized.We also report some simulations in which we try assess the importance of various factors which (presumably) contributed to the economic depression in Finland in 1991-1994.
URN:NBN:fi:bof-20140807132
Keywords: 330